Pine needle surfaces on radial transects across the north boreal area of Finnish Lapland and the Kola Peninsula of Russia - Turunen, Minna; Huttunen, S. (Environmental Pollution, 1996)
To gain an understanding of the characteristics of the needle surfaces of naturally regenerated Scots pine (Pinus sylvestris L.) and their geographical distribution, eight physicochemical variables were investigated within the north boreal forest area. The visibly undamaged needles were collected in autumn 1990 from 114 plots (3-5 pines per plot) along radial transects from the Monchegorsk and Nikel smelters, emitting SO2 and heavy metals, on the Kola Peninsula, Russia, to Finnish Lapland. The needles were examined by scanning electron microscopy (SEM) and measured for surface wettability using the droplet contact angle (DCA) method. Significant geographical south-north and west-east patterns could be observed in needle surface characteristics, correlating with emissions from the smelters and to climate. Despite the slightly higher initial DCAs (61.4-87.6 degrees) towards the north, the pine needle surfaces of the northernmost transects exhibited higher annual needle wettability change (ANWC) and wax erosion rate (AWER), expressed as the reduction in DCAs and epistomatal wax tube distribution (WTD) during one year, respectively, but a lower occurrence of particles and fungal hyphae than those of more southern transects. The higher ANWC was related to higher atmospheric SO2 concentration, and to the lower long-term temperature sum, but not clearly to annual precipitation. In the Monchegorsk smelter area, the current needles exhibited, on average, a 15% higher WTD and seven degree larger DCA, resulting in more hydrophobic needle surfaces than in Finnish Lapland, but during their first year, both the AWER and ANWC, were greatly increased. In Finnish Lapland, 30%, of all the epistomatal wax tubes disappeared from the needle surface during the first year, the value being 70% for the pines located 8 km from the smelter, The mineral composition of the particles deposited on the needle surfaces mirrored that of the minerals being produced by the smelters (e.g. Fe(x)S(x), CuFeS2, Ni(x)S(x), Fe(x)O(x)), Stomatal densities ...